MICROBIAL DIVERSITY AND ITS ROLE IN ENHANCING SOIL FERTILITY: A COMPREHENSIVE REVIEW (The Research of Medical Science Review, 2025)
Soil microbial diversity is of utmost significance in improving and maintaining soil fertility, a prerequisite for sustainable agriculture. Microorganisms-bacteria, fungi, actinomycetes, archaea, and protozoa, perform all soil functions such as nutrient cycling, organic matter decomposition, and soil aggregation and, directly or indirectly, provide an essential nitrogen fixation, solubilization of phosphorus, and mobilization of potassium for the plants. They improve soil structure, moisture retention, pH level regulation, and root growth of nitrogen-fixing rhizobia and mycorrhizal fungi. However, microbial diversity is influenced by several geological factors, namely texture, pH, organic matter, moisture, agricultural practices, and temperatures. Conservation and Sustainable farming practices understand the microbial diversity contribution as organic farming, less tillage, and cropping system diversification support them, whereas normal practices usually reduce it. Modern methodologies like sequenced 16S rRNA, metagenomes, and metatranscriptomes have made a revolutionary change regarding soil microbial community studies for their deep and detailed insights into the structure and function of these parts. Understanding microbial diversity and its interactions helps formulate better soil management strategies. This review emphasizes the importance of microbial diversity for enhancing soil fertility while discussing sustainable agricultural practices in support of maintaining a healthy soil ecosystem.